2017
DOI: 10.1038/nature21356
|View full text |Cite
|
Sign up to set email alerts
|

Extrachromosomal oncogene amplification drives tumour evolution and genetic heterogeneity

Abstract: Human cells have twenty-three pairs of chromosomes but in cancer, genes can be amplified in chromosomes or in circular extrachromosomal DNA (ECDNA), whose frequency and functional significance are not understood1–4. We performed whole genome sequencing, structural modeling and cytogenetic analyses of 17 different cancer types, including 2572 metaphases, and developed ECdetect to conduct unbiased integrated ECDNA detection and analysis. ECDNA was found in nearly half of human cancers varying by tumor type, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
865
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(905 citation statements)
references
References 34 publications
30
865
1
9
Order By: Relevance
“…These regions were lost from the reassembled derivative chromosome 8. Remarkably, such DMs have recently been detected in nearly half of all human cancers and can lead to exceptionally high expression of the corresponding DM-located genes [29] – typically oncogenes and/or genes conferring resistance to therapy [30]. That said, the frequency at which chromothripsis directly contributes to the formation of DMs across varying cancer types is not established.…”
Section: Chromothripsis Driving Tumorigenesismentioning
confidence: 99%
“…These regions were lost from the reassembled derivative chromosome 8. Remarkably, such DMs have recently been detected in nearly half of all human cancers and can lead to exceptionally high expression of the corresponding DM-located genes [29] – typically oncogenes and/or genes conferring resistance to therapy [30]. That said, the frequency at which chromothripsis directly contributes to the formation of DMs across varying cancer types is not established.…”
Section: Chromothripsis Driving Tumorigenesismentioning
confidence: 99%
“…For instance, Sanborn et al [22] published a method to determine full structures of double minutes using WGS data from The Cancer Genome Atlas (TCGA) glioblastoma multiforme (GBM) samples. More recently, AmpliconArchitect was developed for searching and constructing circular DNA structures based on discordant reads [32]. Recent studies have also reported the structural heterogeneity of double minutes in a tumor population in several cancer types, suggesting that they dynamically evolve [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…This entire procedure is illustrated in Figure 1. Although this strategy is very effective for small eccDNAs (like microDNA and spcDNA) it remains difficult to extract the entire circular DNA for the large DMs, for which alternative methods like microdissection (13), array-CGH (39) or direct sequencing of the total DNA (40) can be applied, as sequences on DMs are highly amplified. As the quantity of cfDNAs obtained from body fluids is very limited, when using cfDNAs as starting material, eccDNA enrichment method may need further improvement to increase sensitivity.…”
Section: Methods For Identification and Enrichment Of Eccdnasmentioning
confidence: 99%